HUBUNGAN ANTARA PENGGUNAAN ALAT PELINDUNG DIRI, UMUR DAN MASA KERJA DENGAN KECELAKAAN KERJA PADA PEKERJA BAGIAN RUSTIC DI PT BORNEO MELINTANG BUANA EKSPORT YOGYAKARTA - Handayani, E. Egriana; Wibowo, Trisno Agung; Suryani, Dyah (Universitas Ahmad Dahlan, 2010)
Background: The industrial advancement needed occupational health and safety higher.Accident is case who unwanted occurred and unknown whenever happened., but could beanticipated. Appeared the secured condition from the accident possibility would fluented theworkability company and kept the work productivity. There was some way to decreased workaccident possibility, many method could done by increasing APD utilization frequencies atproduction level. Occupational accident generally caused by many factors and often caused byso many reason.Method: This research was observasional research who done with coss sectional approach thevariable in this research was APD utilization, age, work period as independent variable andoccupational accident as dependent variable. This research was performed at November 2008for all workers of rustic department PT.BMB Eksport Yogyakarta with sample as big as 37workers. The file taking over using questionaire. The result of the research analized by simplelinier regression test. The aims of this research was to know the relationship between apdutilization, age, work period with occupational accident to the rustic department workers PTBMB Eksport Yogyakarta.Result : The result of this research showed that (1) there were strong relationship between apdutilization , age, work period with occupational accident with p value = 0,009. 2) there wasstrong relationship between age with occupation accident p value = 0,018. 3) there was notrelationship between work period with occupational accident p value = 0,813Conclusion: There were relationship between apd utilization, age, with occupational accident,there was not relationship between work period with occupational accident to the rusticdepartment workers PT BMB Eksport Yogyakarta.Keyword : APD utilization, age, work period, occupational accident